AN ANALYSIS OF COLLABORATIVE LEARNING IN READING COMPREHENSION AT THE TENTH GRADE OF SMA NEGERI 2 GUNUNGSITOLI IN 2022/2023 - Zalukhu, Benny (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2023)
This research aims to analyze the use of collaborative learning methods in teaching reading comprehension of descriptive text in class X SMA Negeri 2 Gunungsitoli. This research is a qualitative research to explore certain phenomena. The subjects in this study were an English teacher and 32 class X students of SMA Negeri 2 Gunungsitoli. The instruments used were tests, interviews and interviews. Data was collected by giving tests, questionnaires, and recording teacher answers from interviews. The collected data has analyzed descriptively. The results showed that the use of collaborative learning methods with teachers in reading comprehension activities through classroom learning have been carried out and teachers often use collaborative learning methods. The test results also show that the results of students' abilities are more improved after the collaborative learning method is used with score from the test was 76,5. From the questionnaire, this research showed the students implementing collaborative learning in the classroom with the highest percentage was 79,7 %. Therefore, it can be concluded that the use of collaborative learning has benefits and this method is more effective for encouraging student interaction with other students in understanding a text, so that collaborative learning methods can improve students' reading skills.